Multicenter retrospective comparison of safety and efficacy among three antithrombotic regimens following TAVI - Ren, Yu; Chen, Jing; Wang, Suchun; Jiang, Zhengli; Luo, Hua (Frontiers in Pharmacology, 2025)
ObjectiveThis study comprehensively evaluates the safety and efficacy of three antithrombotic regimens following Transcatheter Aortic Valve Implantation (TAVI), focusing on thrombotic and bleeding complications to provide data-driven insights for optimizing postoperative management.MethodsA retrospective cohort analysis included 58 TAVI patients from two medical centers (from August 2022 to July 2024). Patients were assigned to three regimens post-TAVI: Group A (warfarin for 3–6 months transitioned to lifelong aspirin), Group B (warfarin transitioned to rivaroxaban), and Group C (dual antiplatelet therapy transitioned to aspirin). Key exclusion criteria were concurrent cardiac surgeries and severe hepatic or renal dysfunction. Primary outcomes included transfusion rates, bleeding incidents, and thrombotic events. Secondary outcomes included coagulation parameters [international normalized ratio (INR), prothrombin time (PT), activated partial thromboplastin time (APTT), D-dimer] and postoperative hospital stay duration.ResultsTransfusion requirements did not differ significantly across groups (p = 0.576). However, significant differences were noted in bleeding events (p = 0.034) and hospital stay duration (p < 0.001) among groups. Group B (warfarin transitioned to rivaroxaban) had the lowest bleeding incidence (0%) and the shortest hospital stay (8.71 ± 3.58 days), compared to Group A (37.5%, 14.71 ± 7.61 days) and Group C (30.0%, 7.50 ± 2.84 days). Transfusion requirements and thrombotic event rates were comparable across groups. APTT was significantly prolonged in Group C (p < 0.001), without corresponding clinical bleeding.ConclusionEach antithrombotic regimen presented unique clinical benefits and limitations. Transitioning from warfarin to rivaroxaban was associated with a significantly reduced risk of bleeding and shorter hospital stays. Transitioning from dual antiplatelet therapy to aspirin monotherapy significant prolonged APTT without increasing clinical bleeding events. These findings highlight the importance of tailored antithrombotic strategies to optimize post-TAVI outcomes.